2023
DOI: 10.12944/crjssh.6.1.04
|View full text |Cite
|
Sign up to set email alerts
|

Blacks in the Middle Ages – What About Race and Racism in the Past? Literary and Art-Historical Reflections

Abstract: Undoubtedly, racism is a deeply-anchored problem that continues to vex our world. There is a long history behind it, which can easily be traced back to the Middle Ages and beyond. This article, however, takes into consideration a number of medieval narratives and art works in which surprisingly positive images of Blacks are provided. The encounter with black-skinned people tended to create problems even for the best-intended white intellectuals or poets during the pre-modern era, but the examples studied here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…We realize, in other words, that the critical debate about the harmonious cohabitation of people from different races, religions, and languages, as it originated already in the Middle Ages, appears to carry direct relevance for modern students (Classen 2023). Testing out this topic in workshops and lectures to larger groups of students at Cairo University and elsewhere confirmed that the interest in that time period was uniformly high, irrespective of political and cultural differences between Egypt and the United States (or other countries).…”
Section: Preliminary Conclusionmentioning
confidence: 98%
“…We realize, in other words, that the critical debate about the harmonious cohabitation of people from different races, religions, and languages, as it originated already in the Middle Ages, appears to carry direct relevance for modern students (Classen 2023). Testing out this topic in workshops and lectures to larger groups of students at Cairo University and elsewhere confirmed that the interest in that time period was uniformly high, irrespective of political and cultural differences between Egypt and the United States (or other countries).…”
Section: Preliminary Conclusionmentioning
confidence: 98%